An In Vivo Confocal Microscopic Study of Corneal Nerve Morphology in Unilateral Keratoconus. (21st January 2016) - Pahuja, Natasha Kishore; Shetty, Rohit; Nuijts, Rudy M. M. A.; Agrawal, Aarti; Ghosh, Arkasubhra; Jayadev, Chaitra; Nagaraja, Harsha
Abstract : Purpose. To study the corneal nerve morphology and its importance in unilateral keratoconus. Materials and Methods. In this prospective cross-sectional study, 33 eyes of 33 patients with keratoconus in one eye (Group 3) were compared with the other normal eye of the same patients (Group 2) and 30 eyes of healthy patients (Group 1). All patients underwent detailed ophthalmic examination followed by topography with Pentacam HR and in vivo confocal microscopy (IVCM). Five images obtained with IVCM were analyzed using an automated CCmetrics software version 1.0 for changes in subbasal plexus of nerves. Results. Intergroup comparison showed statistically significant reduction in corneal nerve fiber density (CNFD) and length (CNFL) in Group 3 as compared to Group 1 (p < 0.001 andp = 0.001, resp.) and Group 2 (p = 0.01 andp = 0.02, resp.). Though corneal nerve fiber length, diameter, area, width, corneal nerve branch density, and corneal total branch density were found to be higher in decentered cones, only the corneal nerve branch density (CNBD) was found to be statistically significant (p < 0.01 ) as compared to centered cones. Conclusion. Quantitative changes in the corneal nerve morphology can be used as an imaging marker for the early diagnosis of keratoconus before the onset of refractive or topography changes.